Medicine, money, and morals : physicians' conflicts of interest - Rodwin, Marc A. (New York : Oxford University Press, 1995)
This is the first systematic examination of financial conflicts of interest in medicine. Marc Rodwin examines the evolution of those medical practices and institutions that left the profession open to conflicts of interest and makes clear suggestions for reform.
The Limits of Public Intervention -- Policies for Physicians' Conflicts of Interest -- The Job Ahead -- Incentives, Ethics, Law, and Social Policy -- Table of Acronyms -- APPENDICES -- A: The Concept of Conflict of Interest -- B: Note on Physicians' Divided Loyalties -- C: Bioethics and Medical School Ethics Education -- D: The Sources and Data Used -- E: Excerpts from Medical Codes of Ethics -- Notes -- Acknowledgments -- About the Author -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- Q -- R -- S -- T -- U -- V -- W -- X.
Print version record.
Includes bibliographical references and index.
English.
eBooks on EBSCOhost
Keywords: Medical ethics -- United States; Medical care, Cost of -- Moral and ethical aspects -- United States; Medical care -- United States -- Cost control; Physicians -- Professional ethics -- United States; Conflict of interests; Éthique médicale -- États-Unis.; Soins médicaux -- Coût -- Aspect moral -- États-Unis.; Conflits d'intérêts.; MEDICAL -- Ethics; Conflict of interests; Medical care -- Cost control; Medical care, Cost of -- Moral and ethical aspects; Medical ethics; Physicians -- Professional ethics; United States